Clinical characteristics of COVID‐19 patients evaluated in the emergency department: A retrospective cohort study of 801 cases. Issue 4 (23rd August 2021) - Cotton, Dale M.; Liu, Liyan; Vinson, David R.; Ballard, Dustin W.; Sax, Dana R.; Hofmann, Erik R.; Lin, James S.; Durant, Edward J.; Kene, Mamata V.; Casey, Scott D.; Ghiya, Meena; Shan, Judy; et al.
Abstract: Background: Coronavirus disease 2019 (COVID‐19), the disease caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), has extracted devastating tolls. Despite its pervasiveness, robust information on disease characteristics in the emergency department (ED) and how that information predicts clinical course remain limited. Methods: We conducted a retrospective cohort study of the first ED visit from SARS‐CoV‐2‐positive patients in our health system, from February 21, 2020 to April 5, 2020. We reviewed each patient's ED visit(s) and included the first visit with symptoms consistent with COVID‐19. We collected demographic, clinical, and treatment variables from electronic health records and structured manual chart review. We used multivariable logistic regression to examine the association between patient characteristics and 2 primary outcomes: a critical outcome and hospitalization from index visit. Our critical outcome was defined as death or advanced respiratory support (high flow nasal cannula or greater) within 21 days. Results: Of the first 1030 encounters, 801 met our inclusion criteria: 15% were over age 75 years, 47% were female, and 24% were non‐Hispanic white. We found 161 (20%) had a critical outcome and 393 (49%) were hospitalized. Independent predictors of a critical outcome included a history of hypertension, abnormal chest x‐ray, elevated neutrophil to lymphocyte ratio, elevated blood urea nitrogen (BUN), measured fever, and abnormal respiratory vital signs (respiratory rate, oxygen saturation). Independent predictors of hospitalization included abnormal pulmonary auscultation, elevated BUN, measured fever, and abnormal respiratory vital signs. Conclusions: In this large, diverse study of ED patients with COVID‐19, we have identified numerous clinical characteristics that have independent associations with critical illness and hospitalization.